EU-Japan security cooperation: trends and prospects - Kirchner, Emil J.; Dorussen, Han (Routledge, Taylor & Francis Group, 2019)
EU-Japan security cooperation in context / Emil Kirchner -- Regional security / Thomas Diez and Jun Tsubouchi -- EU-Japan military relations / Hiroyasu Akutsu and Simon Duke -- Non-proliferation / Nicola Casarini and Michito Tsuruoka -- The EU and Japan in the fight against terrorism and organised crime / Raphael Bossong and Sarah Bothe -- EU and Japanese climate and energy security policy / Katja Biedenkopf and Hiroshi Ohta -- Human security: more potential for cooperation? / Sebastian Harnisch and Ken Masujima -- Civil protection: enhancing resilience through collaboration / Han Dorussen, Daisuke Madokoro and Atsushi Tago -- EU-Japan cybersecurity cooperation / George Christou and Yoko Nitta -- The economic security dimension in EU-Japan relations / Thomas Christiansen, Jean-Christophe Defraigne and Hiromasa Kubo -- The EU-Japan security dialogue and migration: a search for common ground / Harlan Koff, Junichi Akashi and Midori Okabe -- New horizons in EU-Japan security cooperation? / Emil Kirchner and Han Dorussen
Includes bibliographical references and index
Keywords: European Union countries -- Relations -- Japan; Japan -- Relations -- European Union countries; European Union countries -- Military relations -- Japan; Japan -- Military relations -- European Union countries; Aufsatzsammlung; Sicherheitspolitik; Außenpolitik; Europäische Union; Japan; Internationale Politik; Sicherheit